Interrogation of genomes by molecular copy-number counting (MCC). - Daser, A; Thangavelu, M; Pannell, R; Forster, A; Sparrow, L; Chung, G; Dear, P; Rabbitts, T (2006)
Human cancers and some congenital traits are characterized by cytogenetic aberrations including translocations, amplifications, duplications or deletions that can involve gain or loss of genetic material. We have developed a simple method to precisely delineate such regions with known or cryptic genomic alterations. Molecular copy-number counting (MCC) uses PCR to interrogate miniscule amounts of genomic DNA and allows progressive delineation of DNA content to within a few hundred base pairs of a genomic alteration. As an example, we have located the junctions of a recurrent nonreciprocal translocation between chromosomes 3 and 5 in human renal cell carcinoma, facilitating cloning of the breakpoint without recourse to genomic libraries. The analysis also revealed additional cryptic chromosomal changes close to the translocation junction. MCC is a fast and flexible method for characterizing a wide range of chromosomal aberrations.